2017
DOI: 10.1016/j.jmii.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, multicenter Phase II study comparing the efficacy and safety of oral nemonoxacin with oral levofloxacin in the treatment of community-acquired pneumonia

Abstract: Either 500 mg or 750 mg of oral nemonoxacin taken once daily for 7-10 days demonstrated high clinical and bacteriological success rates in Chinese adult patients with CAP. Nemonoxacin at 500 mg once daily for 7-10 days is recommended for future Phase III clinical trials. ClinicalTrials.gov identifier: NCT01537250.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…The recovery rate for typical pathogens was 29.3% (290/989). These results were consistent with those observed in other CAP studies [38][39][40][41][42]. The most commonly identified pathogens in all randomized patients were K. pneumoniae, S. pneumoniae, Haemophilus species, and S. aureus (Figure 1).…”
Section: Overall Recovery Ratesupporting
confidence: 91%
See 1 more Smart Citation
“…The recovery rate for typical pathogens was 29.3% (290/989). These results were consistent with those observed in other CAP studies [38][39][40][41][42]. The most commonly identified pathogens in all randomized patients were K. pneumoniae, S. pneumoniae, Haemophilus species, and S. aureus (Figure 1).…”
Section: Overall Recovery Ratesupporting
confidence: 91%
“…An integrated analysis of one Phase III (registration number: NCT01529476) and two Phase II studies (registration numbers: NCT00434291 and NCT01537250) was conducted to compare the commercial dose of oral NEMO 500 mg vs. oral levofloxacin (LEVO) 500 mg for CAP treatment [37][38][39]. This article will review the integrated efficacy results of NEMO vs. LEVO against the common respiratory pathogens isolated from the three Phase II-III trials.…”
Section: Introductionmentioning
confidence: 99%
“…Nemonoxacin is a novel nonfluorinated quinolone with a wide antimicrobial spectrum covering Gram-positive cocci and Gram-negative bacilli, including the common CAP pathogens. One published phase 2 trial and two unpublished phase 3 trials suggest that Nemonoxacin is non-inferior to levofloxacin for the treatment of CAP [92,93].…”
Section: The Evidencementioning
confidence: 99%
“…Different Phase II and III clinical trials have investigated the clinical efficacy and safety of nemonoxacin in the treatment of CAP in comparison with levofloxacin. [48][49][50][51] A recent meta-analysis of most recent phase III trial found that nemonoxacin and levofloxacin had similar clinical cure rates in the treatment of CAP (OR = 1.05, 95% CI, 0.67-1.64). Nemonoxacin also had a similar microbiologic response rate than levofloxacin (OR = 0.89, 95% CI, 0.44 to 1.81).…”
Section: Nemonoxacinmentioning
confidence: 99%